2021
DOI: 10.1108/scm-02-2020-0087
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating food quality: How do quality standards influence contract arrangements? A study on Uruguayan food supply chains

Abstract: Purpose The aim of this paper is to study the influence of quality standards on contract arrangements in food supply chains. Design/methodology/approach A qualitative double case study was conducted on the dairy and citrus sectors in Uruguay. A transaction cost theoretical framework was used. All current public and private quality standards applied by processors were studied in relation to contract arrangements between processors and upstream producers as well as downstream buyers for each sector. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Internal inter-related process coordination help companies improve their operational effectiveness and efficiency along SC (Sroufe and Curkovic, 2008; Wiengarten et al , 2013). The common features found in the literature include information sharing (Disny and Towill, 2003; Sanders, 2008), collaborative decision-making (Tsay, 1999; Aviv, 2001; Groot-Kormelinck et al , 2021) and incentive alignment (Mowat and Collins, 2000; Stranieri et al , 2016; Chen, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Internal inter-related process coordination help companies improve their operational effectiveness and efficiency along SC (Sroufe and Curkovic, 2008; Wiengarten et al , 2013). The common features found in the literature include information sharing (Disny and Towill, 2003; Sanders, 2008), collaborative decision-making (Tsay, 1999; Aviv, 2001; Groot-Kormelinck et al , 2021) and incentive alignment (Mowat and Collins, 2000; Stranieri et al , 2016; Chen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the lack of measures to eliminate or control identified hazards hinders the effective use of hazard analysis of critical control points (HACCP) in all stages of the SC. Therefore, to ensure the application of effective food QSs along an SC, SC members must communicate “farm to table food safety” rather than “farm to table HACCP” (Sperber, 2005) and communicate QSs and quality requirements to provide effective formal and informal quality monitoring mechanisms (Groot-Kormelinck et al , 2021).…”
Section: Thematic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…(2020) developed a cold-chain distribution model with time-window constraints and used it to determine that government time-window schemes could boost food quality, at least in urban settings. Groot-Kormelinck et al. ’s (2021) case-study-based investigation of how quality standards impacted food-chain contracts indicated that supply-chain stakeholders' transaction costs could be lowered if quality standards were aligned with contractual arrangements.…”
Section: Literature Reviewmentioning
confidence: 99%